Pertumbuhan Gereja Lokal Jemaat Melalui Proses Pemuridan - Hasanema Wau (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2023)
There is a fundamental difference between being a disciple and being a follower. There are no shortcuts to high-quality Christianity. This noble goal can only be achieved through the process of discipleship. The outreach and discipleship practiced today should reflect on what is written in the Bible. The examples of discipleship in Scripture should be the pattern of discipleship in the post-modern era. This is what drives the implementation of this research (as an urgency). God's Word applies to all generations, so there must be a breakthrough to find relevance with what’s stated in the Bible. The goal of this writing should reflect on what is written in the Bible for the church to make discipleship as the main strategy in triggering congregational growth, in quality and subsequently quantity growth. Church cannot be satisfied with the overflowing number of visitors at Sunday services. Nor by the grandeur church building, which is indeed the main attraction. A good and proper reason for church satisfaction is the growth born of the discipleship as stated in the Bible. Therefore, it is necessary to design discipleship processes towards life-changing repentance based on simple materials and natural guidance in the community.